Driving towards sustainability: exploring risk perceptions of fossil fuels, e-fuels, and electric drives in individual transport - Rößler, Eva; Schmeckel, Tim; Kesselheim, Ute; Arning, Katrin (Frontiers in Energy Research, 2024)
The transportation sector is a significant contributor to CO2 emissions, necessitating the adoption of alternative drive technologies to achieve decarbonization. This study investigates public perceptions of fossil fuels, e-fuels, and electric drives, with the aim of identifying factors influencing risk perceptions, perceived efficacy in combating climate change, and readiness to use or purchase cars with these technologies. Therefore, a quantitative study using a questionnaire (N = 141) was conducted. The results indicate that e-fuels and electric drives are perceived more positively than fossil fuels. E-fuels were found to have the lowest risk perceptions. Differences in cognitive and affective risk perceptions, as well as in financial, environmental, and health-related risks, were observed across drive types. Car affinity was found to correlate negatively with risk perceptions of e-fuels and fossil fuels, but positively with electric drives. The risk perception of global warming showed an inverse relationship. Regarding the prediction of readiness, differences were found between e-fuels and electric drives in terms of the influencing factors on readiness. The study contributes to the understanding of public perceptions by providing a comparison between different drive technologies and offers valuable insights for developing targeted communication strategies.